CONCEPTS OF AYURVEDA IN SHRIMAD BHAGVAD GEETA - A REVIEW - Pandya, Bhavna (International Journal of Ayurveda and Pharma Research, 2017)
Having philosophical background Ayurveda is very close to Shrimad Bhagvad Geeta. Philosophy presents fundamentals of the principles whereas the science presents the applied aspects of these fundamental principles. The ultimate goal of life is to get rid from all the miseries i.e. from the cycle of birth and death. To attain the salvation, the true knowledge of self and the universe is essential. Triguna i.e., Sattva, Raja and Tamo guna plays an important role regarding the true knowledge. Rajas and Tamas are the prime causes of the diseases, where as the Sattva guna leads towards health. Karma (good and bad deeds) is such a factor which leads an individual to happy or unhappy life respectively. Ayurveda explains in a very well manner the Dos and Donts as a preventive measure. Beyond the medical science Ayurveda explains the life style which leads the human being towards the ultimate goal. Shrimad Bhagvad Geeta also narrates the same guideline for the human being to get Param Pada (salvation). In the present era of very fast and stressful life there are so many pathies for the treatment of the diseases. Among these Ayurveda gives a spiritual touch to the treatment and it is the science of using health as the basis of ones journey toward the supreme power (God). Ayurveda as well as Shrimad Bhagvad Geeta both the scriptures explains the basic concepts such as Srushti aavirbhaav (evolution process), Karma, Triguna, Panch Mahabhuta, Atma tatva, Punarjanma (rebirth), Moksha (salvation), etc. for the sake of human being.